A Quantum-Safe, Interoperable, and Decentralized Payment Infrastructure for the Post-Classical Era as a Strategic Framework for Secure Global Transactions - Mansur, Md. Abul (European Scientific Journal, ESJ, 2025)
The rise of quantum computing introduces a profound threat to existing digital security frameworks, particularly those that underpin modern payment systems. Current cryptographic standards, such as RSA, ECC, and ECDSA are susceptible to being broken by quantum algorithms like Shor’s and Grover’s, jeopardizing the confidentiality, authenticity, and integrity of transactions across financial networks. This study presents a comprehensive investigation into the design, feasibility, and architecture of a universal quantum-safe payment platform capable of processing all types of digital transactions, ranging from mobile money and bank transfers to blockchain-based and card payments through existing delivery channels on a decentralized infrastructure. The research synthesizes current developments in post-quantum cryptography (PQC), including lattice-based, hash-based, and code-based algorithms, and evaluates their suitability for real-time financial systems. The proposed platform incorporates a permissioned distributed ledger, API-level compatibility with legacy financial protocols, and an identity-governed, modular architecture that enables cryptographic agility and policy compliance. Through architectural modeling and critical analysis, this research provides a forward-looking blueprint for building quantum-resilient financial infrastructure. It concludes that while performance and governance hurdles remain, quantum-safe payment networks are both technically feasible and urgently necessary. This work aims to equip stakeholders, especially fintech firms, banks, and regulatory bodies, with a detailed roadmap for transitioning to secure, interoperable, and scalable payment systems in the quantum era.